2005
DOI: 10.1038/sj.npp.1300874
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of Rats with Haloperidol: Lack of an Effect on Brain N-Acetyl Aspartate Levels

Abstract: Proton magnetic resonance spectroscopy ( 1 H-MRS) studies of schizophrenia suggest an effect of the disease or of antipsychotic medications on brain N-acetyl aspartate (NAA), a marker of neuronal viability. We studied in rat the effect of haloperidol on NAA, glutamate, and glutamine in several brain regions where metabolite reductions have been reported in chronically medicated patients with schizophrenia. Two groups of 16 rats each were treated with haloperidol depo (38 mg/kg/month) and vehicle for 6 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 26 publications
3
32
1
1
Order By: Relevance
“…Similarly, following a 6-week exposure to haloperidol and clozapine, we detected no reductions in NAA (Bustillo et al, 2004). Recently two studies with 6 months exposures to haloperidol failed to identify NAA reductions in various cortical regions or hippocampus (Harte et al, 2005;Bustillo et al, 2006), consistent with our current findings. However, Harte et al (2005) did find striatal NAA elevations with haloperidol.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, following a 6-week exposure to haloperidol and clozapine, we detected no reductions in NAA (Bustillo et al, 2004). Recently two studies with 6 months exposures to haloperidol failed to identify NAA reductions in various cortical regions or hippocampus (Harte et al, 2005;Bustillo et al, 2006), consistent with our current findings. However, Harte et al (2005) did find striatal NAA elevations with haloperidol.…”
Section: Discussionsupporting
confidence: 91%
“…Fourth, antipsychotic treatment was not standardized for enrolled subjects. Several studies have suggested that antipsychotic treatment or withdrawal of treatment may raise or reduce cortical NAA levels, respectively (Bertolino Furthermore, a 6-month longitudinal MRS study in haloperidol-treated rats found no effect of antipsychotic treatment on NAA or choline in cortical brain regions (Bustillo et al, 2006). In summary, 12 weeks of davunetide was associated with a modest increase in choline/Cr and a suggestive increase in NAA/Cr in DLPFC in clinically stable people with schizophrenia taking antipsychotic medication.…”
Section: Discussionmentioning
confidence: 93%
“…No changes were observed in other brain areas. Reports from another group did not support these results, and instead these researchers detected no changes in NAA levels in frozen rat brain micro-punches after haloperidol treatment using HPLC (Bustillo et al, 2004) or high field MRS (Bustillo et al, 2005). Further studies are required to determine the effects of haloperidol on brain NAA levels.…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 90%